Novels in Augmented Reality - Stefano Calabrese (Between, 2014)
One of the new forms of storytelling is immersive fiction, a narrative where the text creates events in a simulated world and in which the user is to govern a character or to identify with him, as in a video game. The rise of the World Wide Web and the diffusion of non-sequential reading styles has given birth to a new model of narrative immersivity based on the emotional involvement of the narratee and his/her empathysing with the author; to the point where distinctions become blurred.